(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The canteen is the heart of an academic institution because it serves as the primary source of food for students and employees on campus. It is responsible for the students’ eating habits, which should be healthy. As a result, it is expected that students’ food preferences will have a significant impact on their well-being. Currently, the majority of school canteens face common issues, such as students’ eating habits, the type of food to be sold, high-priced food, small there is alack of space, kitchen facilities, and hygiene. Several students expressed concerns about the BCP canteen. The data presents the details of the analysis and interpretation of collected data from the research questionnaire and recorded scores taken from the results of the questionnaire examinations using a research administrative form. Findings are revealed through the presentation of statistical tables, which show the results of the assessment of the group of workers as respondents of the study. The purpose of this chapter is to summarize the findings that emerged from the study and what the study suggested, revealed, or indicated. This usually refers to the total outcomes rather than the conclusions or recommendations drawn from them.